(untitled) (Research, Society and Development, 2020)
Objective: The aim of this study was to compare pre-competitive anxiety athletes in wrestling and handball, and to verify the relationship of pre-competitive anxiety with age. Methods: Participated in this cross-sectional study 62 athletes (32 Chinese boxing and jiu-jtsu and 20 handball), both genders (55 men and 7 women), with a mean age of 24.25 ± 4.71 years. The instrument used was the reduced version of Competitive State Anxiety Inventory-2 (CSAI-2R). Data analysis was conducted using Generalized Estimation Equations (EGG) and Pearson correlation (p <0.05). Results: The results revealed that handball athletes presented higher cognitive anxiety score (p = <0.001), somatic (p = <0.001) and self-confidence (p = <0.001) when compared to wrestling athletes. No significant correlation was observed between age and anxiety dimensions. Conclusion: It was concluded that the sport seems to be an intervening factor in pre-competitive anxiety in the sports context.